Descripción del efecto producido por el cambio en patrones de cargas cíclicas con frecuencias constantes en acero 1045 (2017)
"This project makes mention to advocate the 1045 steel life when it is submitted under cyclic bending loadswhen their magnitudes vary.This document shows how data follow a normal distribution to reach a linear regresionbetween the logarithm of bending stressand the logarithm od number of cycles.Continued to implementa methodologywherethe bending loads changewith a number of cycles according to Miner's law until the failure with the objective to determine which the cracks behaviour is and what reliability the model has. Furthermore, this methodology tells the linear regresion has a determination coefficient of 97%." -- Tomado del Formato de Documento de Grado.